OVERWEIGHT AND OBESITY: FREQUENCY AND CORRELATES AMONG THE PATIENTS OF FIRST EPISODE OF DEPRESSION - Kazmi, Syed Azhar Ali; Quddus, Abdul; Khan, Muhammad Fareed; Naveed, Faisal; Batool, Syeda Misbah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To study the magnitude and correlates of overweight and obesity among the patients presenting with first episode of depression at a teaching hospital of Azad Jammu and Kashmir. Study Design: Correlational study. Place and Duration of Study: Poonch Medical College Rawalakot, from Jan 2018 to Jun 2018. Methodology: The sample population comprised of 110 patients of first episode of depression reporting in the psychiatry outpatient department at a teaching hospital in Rawalakot, Azad Jammu Kashmir. Depression was diagnosed by using the routine ICD-10 criteria for a depressive episode. Overweight were the patients with BMI 25 or more and obese were with the body mass index 30 or more. Relationship of the age, gender, smoking, family income and lipid profile were studied with the presence of overweight or obesity among these patients suffering from the first depressive episode. Results: A total of 110 patients suffering from first episode of depression were included in the final analysis. Out of these 43 (39.1%) had body mass index in normal range, 24 (21.8%) were overweight while 43 (39.1%) were obese. It was found that female gender and abnormal lipid profile at first presentation had significant association with the overweight or obesity among the target population. Conclusion: Patients with first episode of depressive illness showed high prevalence of obesity and overweight. Female patients suffering from depression and those having abnormal lipid profile indices at first presentation should be considered at a high risk of obesity and overweight.